SGIP1 Deletion in Mice Attenuates Mechanical Hypersensitivity Elicited by Inflammation - Durydivka, Oleh; Kuchar, Martin; Blahos, Jaroslav (Cannabis and cannabinoid research, 2025)
Background: Activation of cannabinoid receptor 1 (CB1R) in the nervous system modulates the processing of acute and chronic pain. CB1R activity is regulated by desensitization and internalization. SH3-containing GRB2-like protein 3-interacting protein 1 (SGIP1) inhibits the internalization of CB1R. This causes increased and prolonged association of the desensitized receptor with G protein-coupled receptor kinase 3 (GRK3) and beta-arrestin on the cell membrane and results in decreased activation of extracellular signal-regulated kinase 1/2 (ERK1/2) pathway. Genetic deletion of SGIP1 in mice leads to altered CB1R-related functions, such as decreased anxiety-like behaviors, modified cannabinoid tetrad behaviors, reduced acute nociception, and increased sensitivity to analgesics. In this work, we asked if deletion of SGIP1 affects chronic nociception and analgesic effect of Δ9-tetrahydrocannabinol (THC) and WIN 55,212-2 (WIN) in mice. Methods: We measured tactile responses of hind paws to increasing pressure in wild-type and SGIP1 knock-out mice. Inflammation in the paw was induced by local injection of carrageenan. To determine the mechanical sensitivity, the paw withdrawal threshold (PWT) was measured using an electronic von Frey instrument with the progression of the applied force. Results: The responses to mechanical stimuli varied depending on the sex, genotype, and treatment. SGIP1 knock-out male mice exhibited lower PWT than wild-type males. On the contrary, the female mice exhibited comparable PWT. Following THC or WIN treatment in male mice, SGIP1 knock-out males exhibited PWT lower than wild-type males. THC treatment in SGIP1 knock-out females resulted in PWT higher than after THC treatment of wild-type females. However, SGIP1 knock-out and wild-type female mice exhibited similar PWT after WIN treatment. Conclusions: We provide evidence that SGIP1, possibly by interacting with CB1R, is involved in processing the responses to chronic pain. The absence of SGIP1 results in enhanced sensitivity to mechanical stimuli in males, but not females. The antinociceptive effect of THC is superior to that of WIN in SGIP1 knock-out mice in the carrageenan-induced model of chronic pain.
Keywords: Morpholines; morfoliny; Naphthalenes; Dronabinol; nocicepce; Female; naftaleny; Inflammation; Hyperalgesia; zvířata; myši; zánět; myši inbrední C57BL; Mice; myši knockoutované; tetrahydrokanabinol; ženské pohlaví; Male; Mice, Knockout; receptor kanabinoidní CB1; benzoxaziny; Mice, Inbred C57BL; hyperalgezie; Nociception; Animals; Receptor, Cannabinoid, CB1; mužské pohlaví; Benzoxazines